BUDAYA KERJA SEBAGAI MEDIASI BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PEGADAIAN REGIONAL XII SURABAYA - Rahardjo, Surjo; Prasetyo, Indra (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
This study aims to analyze the effect of workload and work environment on employee performance, and explore the role of work culture as a mediator at PT. Pegadaian Regional Office XII Surabaya. This study uses a quantitative approach. The population is 664 employees and the sample is 244 employees selected through a multistage sampling technique, which combines proportional cluster random sampling and purposive sampling. The results of the study indicate that workload and work environment have a significant effect on employee performance. Although work culture has a significant effect on employee performance, work culture does not mediate the effect of workload on performance. Work culture successfully mediates the effect of work environment on employee performance. This finding implies that good workload management and the creation of a conducive work environment can improve employee performance, with a strong work culture as an important factor in mediating the effect of work environment.